Effect of Effective Microorganisms (EM 4) on the Growth of a Variety of Upland Rice Varieties in Swampy Areas - Iqbal, Muhammad; Rosmiah, Rosmiah; Gusmiatun, Gusmiatun (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2015)
The research aims to identify and study the dose of EM 4 administration on the growth and production of some of the best in upland rice varieties in swampy areas. This research activity has been carried out from the month of June to September 2014. This study This study used a split-plot design as the main plot treatments were: 4 EM dose and treatment of children's plot is a variety of upland rice varieties and each repeated 3 times. Yag factors examined in this study include the dose of EM 4 5 ml / l, 10 ml/ l and 15 ml / l while the varieties used are varieties Situ bangendit, Huma and Andalas parameters observed in this study is the High Plant (cm ), 2. Maximum Number of Tillers, 3. The number of productive tillers, panicles 4. length (cm), 5. Total Grain Permalai, 6. Number of Contents Grain, Grain Perumpun 7. weight (g), 8. Percentage of Grain Vacuum (% ), 9. 1000 grain weight. 10. Production Perpetak. The results can in this study is the interaction between treatment dose administration of EM 4 15 ml / l and the use of varieties Situbagendit showed good results on the growth and yield of rice Gogo in swampy areas.